On the curry trail : chasing the flavor that seduced the world : in 50 recipes - Iyer, Raghavan, 1961- (Workman Publishing, 2022)
"On the Curry Trail is an enlightening journey across Australia, Asia, Africa, Europe, and the Americas to explore the origins of curry and the signature, essential curries of each region. This diaspora of curry brings alive not only the most iconic, category-defining recipes from these continents, but also the history, lore, anecdotes, and familial remembrances that fashion each dish. It delves into the story of curry: What it was and what it is, the places to which it has traveled and the ways it has evolved (whether because of local ingredients, cultural tastes, or other factors). And the book embraces the many interpretations and definitions of this beloved dish. It makes the flavors of these scintillating curries accessible to the everyday home cook. On the Curry Trail is at once a mash note and an education (one rich in history and sense of place) that tells the definitive, delectable story of this beguiling dish in 50 irresistible recipes. Illustrations throughout"--